Effectiveness of BUMDes Management in Bale Village, Tanantovea District, Donggala Regency - Nurhannis, Nurhannis; Al-Kafiah M. Samsu, M. Kafrawi; Maman Firmansyah, Andi; Ariyani, Risma (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
BUMDes was formed in order to succeed the village fund program established by the central government. With the establishment of BUMDes, the focus of the utilization of village funds is no longer on the development of village facilities and infrastructure but rather on community empowerment as an effort to improve the welfare of village communities. BUMDes is formed by the village government and on the initiative of the village community so that the formation of BUMDes is based on community needs and village potential. As a new institution in the village, the management of BUMDes is not only as an institution with the aim of gaining profit but as a non-profit institution that is tasked with empowering the village community. Community empowerment aims to increase the knowledge, understanding and skills of village communities in productive economic activities implemented by BUMDes.